Optimizing Resin Infiltration Procedure in Molar Incisor Hypomineralization Lesions - Torres, Carlos Rocha Gomes [UNESP]; Pereira, Talita Portela [UNESP]; Effenberger, Susanne; Borges, Alessandra Bühler [UNESP] (Wiley, 2024)
Objective: This article aims to describe a new technique for predicting the results of resin infiltration procedure in molar incisor hypomineralization lesions, named Infiltration Monitoring by Transillumination. The technique involves the use of transillumination together with ethanol application during the steps of lesion body opening and resin penetration. It provides color contrast that enhances the removal of the less porous surface layer and controls the effectiveness of resin infiltration within the lesion. Clinical Considerations: The clinical procedure presented illustrates the steps involved in the resin infiltration procedure for color masking of molar incisor hypomineralization lesions in anterior teeth, highlighting the use of transillumination both for monitoring the lesion body opening step and the resin infiltration process. Conclusions: The monitoring with transillumination during the ethanol test can assist the removal of the enamel external layer over the lesion, necessary to expose the inner porosity to be infiltrated, in a very precise and conservative way. In addition, it can effectively help to determine the moment when the infiltrant resin has fully penetrated the lesion. Clinical Significance: The Infiltration Monitoring by Transillumination technique offers the possibility to precisely control the infiltration procedure in molar incisor hypomineralization lesions, thereby improving the predictability of the esthetic outcome.
Keywords: color masking; esthetic; molar incisor hypomineralization; resin infiltration; transillumination